Expression and prognostic analysis of PFKFB4 in oral squamous cell carcinoma: PFKFB4 in oral squamous cell carcinoma - Chen, Shuting; Han, Jiusong; Wang, Wei; Wu, Zhengzheng; Wang, Juan; Cheng, Bin (Cellular and Molecular Biology, 2024)
Fructose-6-phosphate 2-kinase/fructose-2,6-bisphosphatase 4 (PFKFB4) is a crucial enzyme in the glycolysis pathway, possessing both kinase and phosphatase capabilities. Although it has emerged as an important oncogene in various cancer types, its function in oral squamous cell carcinoma (OSCC) is still not well understood. In our research, PFKFB4 expression was assessed via immunohistochemical (IHC) staining of tissue microarrays and OSCC patient specimens. The transcriptional expression of PFKFB4 in OSCC was analyzed by utilizing The Cancer Genome Atlas (TCGA) dataset. Correlation between PFKFB4 expression and clinicopathological features was examined using the χ2 test. Prognostic investigation of PFKFB4 was conducted via Kaplan-Meier and Cox analyses. PFKFB4 levels were notably elevated in OSCC samples in comparison to adjacent normal tissues (P < 0.001). Elevated PFKFB4 expression was associated with higher histologic grade (P = 0.0438), higher T stage (P = 0.031), and more advanced clinical stage (P = 0.0063). The ROC curve demonstrated the diagnostic potential of PFKFB4 (AUC = 0.827). Increased levels of PFKFB4 were linked to decreased overall survival (OS) (P = 0.04), poorer disease-specific survival (DSS) (P = 0.04), and shorter progression-free interval (PFI) (P < 0.001). PFKFB4 expression was identified as an independent risk factor for OS based on Cox regression analysis [hazard ratio (HR) = 1.517, P = 0.044)]. An OS nomogram was constructed with a concordance index of 0.690. Our findings reveal that upregulated PFKFB4 expression in OSCC tissues could serve as a potential prognostic biomarker.